The Earnings Management Motivation: Accrual Accounting vs. Cash Accounting - Dr. Sandeep Goel (Australasian Accounting, Business and Finance Journal, 2016)
The Accrual basis of accounting has always found favour amongst corporate practitioners of earnings management. There have been extensive studies on earnings management, focusing on earnings hazards. This paper contributes to the literature by showing market inclination to accrual basis of accounting as motivated by a desire for earnings management. It analyzes the sample units’ performance in regard to accrual-indicators vs. cash-indicators and their pervasiveness on stock pricing in India. In India, the corporate ownership model is the Promoter Dominated Shareholders Model (PDSHM) which makes this study unique in highlighting earnings management motivation. The units show a market preference for accrual numbers and motivation for earnings management as clear in their stock pricing behavior. I hope the study improves investors’ perception of the reliability of a firm’s performance, as measured by earnings. It is of use to the users of financial accounting and corporate finance globally for rationalizing the motivation behind earnings manipulation by the management.
Keywords: Accrual basis; cash basis; accounting indicators; stock pricing; earnings management